PERKEMBANGAN SISTEM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA BERDASARKAN HUKUM TATA NEGARA - Stanley Kurniawan (Jurnal Hukum Adigama, 2021)
Law is a system of regulations in which norms and sanctions are made with the aim of controlling human behavior to protect discipline, justice, and avoid the formation of chaos. Each country has certain legal rules that are different from other countries, including Indonesia. That means "every citizen is obliged to obey the laws and regulations that apply in Indonesia". With the law, the crime rate can be minimized, and also the power holder cannot act arbitrarily because it has been limited by law. In addition, the law helps to protect the rights and obligations of every citizen. Therefore, the state must have a proper legal system. The law also has several purposes, with the law, the prosperity of society will be guaranteed. All laws that apply in any country must have their own elements. That way, the applicable law can be recognized by the citizens of that country. Constitutional law is also a branch of law that regulates legal norms and principles written in state practice. Constitutional law regulates matters relating to the state, such as the forms and structures of the state, state duties, state equipment, and relations with state equipment.